Analysis of Self-Management Dietary Behavior Levels Among Seventh-Semester Students at the Faculty of Public Health, Campus IV, State Islamic University of North Sumatra, 2024 - Nurhazizah; Syahrida Suryani Hasibuan; Annisa Rizki Ramadani Siregar; Raspiyahni (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2025)
College is a crucial transitional period in a person's life, with significant lifestyle changes, including dietary patterns and health behaviors. Self-Management Dietary Behaviors (SMDB) are crucial aspects that influence students' health and academic performance. Self-Management Dietary Behaviors encompass an individual's ability to manage their food intake in a way that supports long-term health. This study is a quantitative study using a questionnaire as a data collection technique. The purpose of this study was to analyze the level of Self-Management Dietary Behaviors (SMDB) among students at the Faculty of Public Health, State Islamic University of North Sumatra. The results showed that the majority of respondents (89.9%) had a moderate level of SMDB, while 8.9% had a low level, and 1.3% had a high level. Factors influencing BMI include gender, age, and Body Mass Index (BMI), with significant associations between gender (p=0.035), age (p=0.041), and BMI (p=0.006 for national criteria and p=0.008 for WHO criteria) and BMI levels. This study also found that students with abnormal BMI, both underweight and obese, had lower BMI levels. Therefore, tailored nutrition interventions are needed, including gender- and age-specific nutrition education, increased access to healthy foods on campus, psychosocial support for at-risk groups, and flexible time for nutrition activities. This study emphasizes the importance of managing healthy eating patterns among students to improve their quality of life.